2008
DOI: 10.1007/s11430-008-0135-z
|View full text |Cite
|
Sign up to set email alerts
|

Relocation of the M8.0 Wenchuan earthquake and its aftershock sequence

Abstract: We relocated M8.0 Wenchuan earthquake and 2706 aftershocks with M≥2.0 using double-difference algorithm and obtained relocations of 2553 events. To reduce the influence of lateral variation in crustal and upper mantle velocity structure, we used different velocity models for the east and west side of Longmenshan fault zone. In the relocation process, we added seismic data from portable seismic stations close to the shocks to constrain focal depths. The precisions in E-W, N-S, and U-D directions after relocatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
103
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(119 citation statements)
references
References 13 publications
13
103
1
2
Order By: Relevance
“…The location and orientation of the line fault is in good agreement with the aftershock distribution (Huang et al 2008; Fig. 1).…”
Section: A P P L I C At I O N T O T H E 2 0 0 8 M W 7 9 W E N C H Usupporting
confidence: 74%
“…The location and orientation of the line fault is in good agreement with the aftershock distribution (Huang et al 2008; Fig. 1).…”
Section: A P P L I C At I O N T O T H E 2 0 0 8 M W 7 9 W E N C H Usupporting
confidence: 74%
“…(b) Three-dimensional geometry of the main fault and discrete slip on patches. The white dots show aftershocks up to 22 July 2008 (Huang et al, 2008).…”
Section: Data Compilationmentioning
confidence: 99%
“…The parameters are taken from CRUST2.0 (Mooney et al, 1998) (see Table 1). Based on the aftershock distribution (Huang et al, 2008) and the mapped surface ruptures identified in the field survey (Liu et al, 2008;Zhang et al, 2008), we then design a double-fault source model. The main Beichuan fault is divided into two segments: the NE segment is 120 km, striking N228.5…”
Section: Parameter Settingmentioning
confidence: 99%
“…The earthquake propagated unilaterally to the northeast, leaving the southern segments of the LMSF (hereafter refered to as the southern LMSF) unbroken [9,10] (Figure 1). In addition, the southern LMSF accommodated few aftershocks [11]. On 20 April 2013, the Mw 6.6 Lushan earthquake ruptured the southern LMSF and filled part of the rupture deficit along the southern LMSF [12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the southern LMSF accommodated few aftershocks [11]. On 20 April 2013, the Mw 6.6 Lushan earthquake ruptured the southern LMSF and filled part of the rupture deficit along the southern LMSF [12].…”
Section: Introductionmentioning
confidence: 99%